Unlocking Renewable Potential in Logistics Hubs: Policy Frameworks for Inclusive Energy Transitions - Loso udijanto; Untung Lestari Nur Wibowo; Dimas Endrawan Putra (Indonesian Scientific Publication, 2025)
Logistics hubs play a vital role in global decarbonization due to their high energy use and strategic position within supply chains, yet they are often excluded from national renewable energy policies. This exclusion limits their potential to become active clean energy producers. This study examines the regulatory and institutional barriers that hinder renewable energy integration in logistics hubs and proposes an inclusive policy roadmap tailored for this sector—offering a novel contribution beyond prior studies focused on residential and industrial contexts. Using a comparative methodology, the research analyzes energy regulatory frameworks across Germany, Brazil, the UAE, Indonesia, and the United States. Data were collected from government reports, institutional documents, and peer-reviewed studies. A hybrid analytical framework combining stakeholder mapping and policy categorization was employed to identify existing gaps and opportunities. The findings show that logistics hubs are frequently excluded from mechanisms such as net metering, feed-in tariffs, and tax incentives due to outdated classifications that overlook their dual industrial-service roles. Case studies from Germany, Brazil, and the UAE highlight the effectiveness of targeted measures like grid fast-tracking, specific subsidies, and integrated municipal approaches in advancing renewable adoption. Furthermore, strong public-private partnerships and dynamic pricing systems are key to aligning logistics operations with renewable goals. The study concludes that infrastructure development must be complemented by policy innovation through harmonized, inclusive, and multi-level governance to embed logistics hubs effectively in renewable energy strategies.